Does extracurricular sports have an impact on quality of life? - Jajiyah, Nur Khois; Gumilar, Agus; Mudjihartono, Mudjihartono; Negara, Jajat Darajat Kusumah; Hambali, Burhan (Jurnal Patriot, 2024)
Problems: Extracurricular sports activities at school are activities outside of school that are the only physical activities carried out regularly every week and are expected to have a significant impact on the quality of life of teenagers, considering the low quality of life in society. Purpose: To reveal the impact of extracurricular sports activities on the quality of life of high school students. Methods: This research uses a descriptive approach, namely by conducting a survey about the quality of life of high school students. This research involved 332 respondents, coming from schools in the northern part of West Java and with active student status. The instrument used is the WHOQOL-BREF quality of life questionnaire developed by the World Health Organization, consisting of four indicators: physical health, social relationships, psychology, and the environment. Results: The results of the analysis show that extracurricular sports have a significant impact on the quality of life of high school students. It is an interesting finding that participating in extracurricular sports at school contributes positively to improving students' quality of life. Conclusion: The role of extracurricular activities in schools is very important for improving students' skills, increasing their motivation, increasing their potential based on interests and talents, and improving the quality of life. It is hoped that this can be a recommendation for related parties to socialize for extracurricular activities more often in the school environment.